MECHANISMS ON FINANCIAL PERFORMANCE OF IRAQI STOCK EXCHANGE - Talib Hashim, Dr. Hasan; Jasim, Mawj Abbas; Izumi, Tamara (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
This paper examines the financial impact of the mechanisms of internal corporate governance in the context of the Iraqi Stock Exchange (ISX). A quantitative research design was selected to answer the research questions and five hypotheses. Sixty items were used to measure the effects of the internal corporate governance mechanisms on the financial performance of the ISX. A sample consisting of Iraqi Stock Exchange branches was chosen using the standardized random sample technique. The data analysis using SPSS version 25 and SmartPLS 3.28 showed the positive impact of the internal corporate governance mechanisms on the financial performance of the ISX. This result showed the significance of Board Committees in improving financial performance ( beta0.137; t4.343; p0.001). Likewise, the result also showed the significant impact of Board of Directors on financial performance (beta0.217; t7.771; p0.000). Financial Statements & Auditors also pose a major significant impact on financial performance ( beta0.296; t6.508; p0.000), as does Ownership Structure (beta0.209; t4.607; p0.000). Lastly, Stock-Based Compensation was also shown to pose an impact on financial performance ( beta0.167; t3.389; p0.001). This study's practical contribution is in addressing the weak financial performance of Iraqi commercial companies and urging the adoption of internal governance elements to solve the problems between management and shareholders, which helps reduce risks and corporate collapse as well as boost financial performance.